Development of white brick fuel cell using rice husk ash agricultural waste for sustainable power generation: A novel approach. (December 2021) - Magotra, Verjesh Kumar; Lee, S.J.; Inamdar, Akbar I.; Kang, T.W.; Walke, Pundalik D.; Hogan, Stephanie C.; Kim, D.Y.; Saratale, Ganesh D.; Saratale, Rijuta G.; Purkayastha, Anwesha; Jeon, H.C.
Abstract: The paper focuses on fabricating a white cement brick fuel cell (WC–BFC) using agricultural waste rice husk ash (RHA) for sustainable power generation. The samples from each material with three different compositions 0, 2, and 12% of RHA were analysed. First with (RHA + sand) and (RHA + sand + cement) for commercial brick technology. This study aims to replace the present ordinary old concrete brick with WC-BFC technology in the market. Steel is an essential material used in concrete for longs decades due to its strength and stability. Therefore, the brick cost depends on the type of electrode used for brick fabrication. However, Ammonium chloride 0.3 g/ml was used as fuel with regular intervals of time for WC-BFC. Where steel/graphite electrodes generate a higher power density of 2008.93 mW/m 2 with 12% RHA concentration and later for long life electrodes, Graphite/Graphite is also optimised to see the effect on the power. These bricks themselves generate massive free power from their own. The proposed technology is eco-friendly, inexpensive, sustainable, and compatible with generating renewable energy for vast brick commercial applications. On one side work as a regular concrete brick, and another side free power supply. This technology itself is clean, safe, and sustainable. Graphical abstract: Image 1